Study on the Vibration Propagation Law and Stress Distribution Characteristics in Double-Arch Tunnels During Blasting - Xiaofei Sun; Ying Su; Dunwen Liu; Yu Tang; Pei Zhang; Jishuang Hu; Xianghao Sun (Buildings)
Highway tunnel construction in mountainous areas of China has been developing rapidly. The influence of drilling and blasting on the existing tunnel structure has become a key factor affecting the safety and stability of tunnel construction. The double-arch tunnel has unique structural characteristics. The propagation characteristics of blasting vibrations and the resulting stress responses exhibit a certain level of complexity. There is little research on the influence of single-line blasting excavation of double-arch tunnel on the other line tunnel. This paper analyzes the blasting vibration of a double-arch tunnel by ANSYS/LS-DYNA. The propagation law of blasting vibration velocity and stress distribution law of blasting vibration in different sections of the tunnel is revealed. At the same time, the relationship between the peak particle velocity (PPV) and tensile stress is established, and the threshold vibration velocity is proposed. It provides a scientific basis for tunnel design and construction. The propagation of blasting vibration in the adjacent roadway is affected by the middle pilot tunnel. The peak vibration velocity of different parts decreases with the increase in distance. The monitoring of vibration velocity and stress in section A of the right line of the adjacent tunnel should be strengthened, especially in the tunnel vault, blast-facing side wall, and arch foot. The difference in vibration strength across different tunnel parts provides a basis for optimizing the structure. It helps strengthen the parts susceptible to vibration during the design stage of the multi-arch tunnel, improving the tunnel’s safety and stability.